Nutritional status of cancer patients in chemotherapy; dietary intake, nitrogen balance and screening - Gudny Geirsdottir, Olof (CoAction Publishing, 2008)
OBJECTIVE: To evaluate a short screening sheet (SSM) for malnutrition and to investigate the nutritional status of patients receiving chemotherapy for cancer of the lungs, colon or breast at an outpatient clinic. DESIGN: Full nutritional assessment was conducted to define malnutrition and validate the SSM. Additionally, weight change from earlier healthy weight was evaluated, and calculations for intake of energy-giving nutrients (three-day-weighed food records) and protein balance were performed. After the evaluation study, the SSM was tested in clinical routine and data collected about patients’ need for nutritional counseling. SUBJECTS: Patients at the outpatient clinic of the Department of Oncology at Landspitali-University Hospital (n=30 with lung-, colon- or breast cancer in the study population, n=93 with all cancer type in clinical routine screening). RESULTS: Malnutrition was defined by full nutritional assessment in 20% of the participating patients and SSM had high sensitivity and specificity. Declining nutritional status of the patients was seen as a negative nitrogen balance and unintentional weight loss from healthy weight, but not as total energy intake, recent weight loss or underweight. The test of SSM in clinical routine showed that 40% were malnourished. According to the patients, 80% needed nutritional counseling but only 17% had such counseling. CONCLUSION: Screening (SSM) for malnutrition in cancer patients is a valid simple approach to define cancer patients for nutritional care. More patients regard themselves in need for nutritional counseling than the number of patients really achieving any.